The Randstad: A Research and Policy Laboratory
XII, 266 p.
Keywords: Randstad Holland is the urbanized western part of the Netherlands. It contains the four largest cities of the country: Amsterdam, Rotterdam, The Hague and Utrecht. The name Randstad (rim city) refers to the distinctive shape of the conurbation, a horseshoe of cities around an open agricultural and recreational area, known as the Green Heart. This book analyzes the restructuring of the region. The volume summarizes the research of the Urban Networks research program. The discussion is focused on four themes: housing, labor market and employment, infrastructure and transportation, and the provision of public services. The Randstad is internationally known as the playground of urban and regional planners. Their debates on present policy issues are extensively reviewed in the book. Teachers and students of urban change and planning, and policy makers and planners in The Netherlands and abroad will find much valuable information in this book.